Web-Based Instrument Development Workshop as Supporting Materials for Online Learning - Isnanik Juni Fitriyah; Sugiyanto Sugiyonto; Erni Yulianti; Novida Pratiwi; Muhammad Fajar Marsuki; Siti Mualifah; Muhammad Adi Widodo (Procedia of Social Sciences and Humanities, 2021)
The development of information and communication technology is currently driving the development of internet networks around the world. This internet can be useful in various fields including education. Education is currently experiencing system changes as a result of the COVID-19 pandemic. The learning is carried out online. Therefore, it takes teacher skills in preparing online learning media. Based on this, a web-based instrument development workshop activity was carried out for science teachers in the IPA MGMP of Jombang Regency. The number of participants was 65 science teachers in the IPA MGMP of Jombang Regency. The workshop was held for three days online via the zoom platform. The first two days were the delivery of learning video development materials using the OBS application, google form, quizizz and google classroom then the participants worked independently. The third day was a presentation of the participants' independent work. The workshop participants were enthusiastic about participating in the workshop as seen from the zpost-workshop survey results. This workshop resulted in 60 web-based instrument products and articles on the development of participant instruments.